PENERAPAN FUZZY INFERENSI DALAM SELEKSI KAYU MENTAH UNTUK PERABOT BERBASIS METODE MAMDANI - Zain, Zabur; Fajrin, Alfannisa Annurullah (Computer Science and Industrial Engineering, 2020)
ABSTRACT Technology has become a significant part that cant separated in the modern world, especially in the industrial field where so many manufactures competing to fulfil the end-user expectation. At Industry Revolution 4.0, a common problem that occurs in every industry growth is the adoption technology that needs to integrate into the traditional method so the product generation is much faster because optimized. Furniture manufacture is one from a thousand manufacture field that struggles with this condition. The craftsmen are facing the problem with selecting the appropriate raw wood material for production, so the crafted furniture will maintain good quality and makes the creation much efficient. With fuzzy logic Mamdani method, a system will be built and aim to help the manufacturer to determine the best raw material for producing the furniture. The result found that the fuzzy logic Mamdani method is capable of assisting the manufacturer in determining the right raw material to use and achieving a high-efficiency material consumption for the better production cycle. Keywords: Keywords: Furniture; Fuzzy Logic; Mamdani Method: Wood Raw Material.